How Does Explicit Versus Implicit Risk Information Influence Adolescent Risk‐Taking Engagement?. (30th June 2017) - Osmont, Anaïs; Moutier, Sylvain; Simon, Grégory; Bouhours, Lison; Houdé, Olivier; Cassotti, Mathieu
Abstract: Adolescents have been shown to be more likely to engage in risky behaviors in daily life. Many studies have indicated that adolescents could make advantageous choices when they receive explicit information but could fail to choose advantageously when they are not informed about risks. The current study aimed to examine the influence of explicit risk information (i.e., when risk information is directly available) versus implicit risk information (i.e., when risk information has to be learned from feedback) on risk‐taking engagement, in order to clarify whether the enhanced risk‐taking observed in decision making under ambiguity in adolescents results from either a greater exploration of ambiguous situations (i.e., a higher ambiguity tolerance) or a specific difficulty associated with learning based on previous choices' outcomes. Adolescents and young adults completed a new adaptation of the Balloon Analogue Risk Task. They were required to accumulate as many points as possible by inflating balloons associated with variable break points and avoiding explosions. This adaptation involved a manipulation of the information level with two conditions, an "informed" condition and a "noninformed" condition, in which the participants had to learn the matching of colors with balloons' resistances based on feedback. The results demonstrated that providing explicit risk information allows adolescents to be as efficient as adults at the end of the game. In contrast, adolescents failed to adjust risk‐taking to the balloon resistance in the noninformed condition. These findings critically suggest that this failure reflects a specific impairment of feedback‐based learning ability but not a global excess of risk‐taking during adolescence. Copyright © 2017 John Wiley & Sons, Ltd.